2022
DOI: 10.2196/preprints.38067
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TEO: Assessing the Impact of Conversational AI in the Treatment of Stress and Anxiety in Aging Persons: A Randomized Controlled Trial Study (Preprint)

Abstract: BACKGROUND While mental health applications are increasingly available for large populations of users, there is a lack of controlled trials on the impact of such applications. An important population segment includes the senior adults. AI-empowered agents are evaluated when assisting adults with cognitive impairments, while few applications are available for aging adults who are still in their active working life. Those persons often suffer from high levels of stress related to changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The identified studies (n=29) were mostly conducted in the USA (n=10), Sweden (n=6), and the UK (n=6). The studies included a diverse sample of adults (n=22), college students and young adults (n=4), anonymous users (n=2), and adolescents (n=1) ( 28 33 , 41 , 73 94 ). Eight studies reported on the ethnicity of the participants ( 30 , 32 , 41 , 74 , 76 , 77 , 80 , 83 ), and in most of the studies between 31% and 91% of the participants identified as White.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The identified studies (n=29) were mostly conducted in the USA (n=10), Sweden (n=6), and the UK (n=6). The studies included a diverse sample of adults (n=22), college students and young adults (n=4), anonymous users (n=2), and adolescents (n=1) ( 28 33 , 41 , 73 94 ). Eight studies reported on the ethnicity of the participants ( 30 , 32 , 41 , 74 , 76 , 77 , 80 , 83 ), and in most of the studies between 31% and 91% of the participants identified as White.…”
Section: Resultsmentioning
confidence: 99%
“…The meta-analysis assessing the impact of AI-augmented interventions on mental health symptoms considered n=10 studies ( 41 , 73 78 , 80 , 84 , 90 ) presenting pre- and post-intervention outcomes. The results of this meta-analysis showed that these interventions had a significantly large effect size in the reduction of mental health symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations